Nature matrix : new and selected essays - Pyle, Robert Michael (Counterpoint, 2020)
A selection of nature-themed essays by the biologist author of Magdalena Mountain explores such subjects as his early years as a national park ranger, the “wilderness” of modern times and the life of Vladimir Nabokov.